Analysis of Cadmium (Cd) Heavy Metal Content in Mosambique Tilapia Fish (Oreochromis mossambicus) Derived from Rawa Taliwang Lake to Enrich Ecotoxicology Lecture Material in 2022 - Alda Saputri; Khairuddin Khairuddin; M. Yamin (Jurnal Biologi Tropis, 2023)
Rawa Taliwang Lake is used as a tourist spot, recreation, irrigation of agricultural land and fishing grounds by local fishermen. Increased community activity around the lake causes heavy metal pollution to enter the waters. The purpose of this study was to determine the levels of cadmium (Cd) in mosambique tilapia fish from Rawa Taliwang Lake thus enrich ecotoxicology lecture material and find out whether mosambique tilapia fish from Rawa Taliwang Lake is still safe for consumption based on the Food and Drug Control Agency (BPOM) Regulation No. 9 of 2022 concerning requirements for heavy metal contamination in food processing. Sampling used a purposive sampling method and analysis of cadmium using Atomic Absorption Spectrophotometer. The results showed that the concentration of cadmium heavy metal in mosambique tilapia fish 0,1977 mg/kg and it is still safe for consumption by the public because it still below 0,30 mg/kg. Suggested further research regarding analysis of metals in various types of fish and fish body tissues such as kidneys, liver and gills as a comparison.